2016
DOI: 10.1530/eje-15-0642
|View full text |Cite
|
Sign up to set email alerts
|

ARMC5 mutations in a large French-Canadian family with cortisol-secreting β-adrenergic/vasopressin responsive bilateral macronodular adrenal hyperplasia

Abstract: Background: Bilateral macronodular adrenal hyperplasia (BMAH) is a rare cause of Cushing's syndrome (CS) and its familial clustering has been described previously. Recent studies identified that ARMC5 mutations occur frequently in BMAH, but the relation between ARMC5 mutation and the expression of aberrant G-protein-coupled receptor has not been examined in detail yet. Methods: We studied a large French-Canadian family with BMAH and sub-clinical or overt CS. Screening was performed using the 1-mg dexamethasone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 34 publications
1
27
0
4
Order By: Relevance
“…In many cases, large macronodules up to 5 cm or more are encountered; in fact, size as a predictor of malignancy is not relevant in PBMAH since it is an invariably benign entity. Attenuation values above 10 HU (Bourdeau et al 2016) and increased FDG uptake (Alencar et al 2011) have been reported. On MRI imaging the adrenals are hypointense compared with the liver on T1-weighted images and often hyperintense relative to liver on T2-weighted images (Doppman et al 2000, Lacroix 2009).…”
Section: Imaging Characterizationmentioning
confidence: 96%
See 1 more Smart Citation
“…In many cases, large macronodules up to 5 cm or more are encountered; in fact, size as a predictor of malignancy is not relevant in PBMAH since it is an invariably benign entity. Attenuation values above 10 HU (Bourdeau et al 2016) and increased FDG uptake (Alencar et al 2011) have been reported. On MRI imaging the adrenals are hypointense compared with the liver on T1-weighted images and often hyperintense relative to liver on T2-weighted images (Doppman et al 2000, Lacroix 2009).…”
Section: Imaging Characterizationmentioning
confidence: 96%
“…Subsequent studies confirmed that ARMC5 mutations are common in patients with PBMAH . They account for the vast majority of familial cases (13 out of the 16 reported families) , Gagliardi et al 2014, Elbelt et al 2015, Suzuki et al 2015, Bourdeau et al 2016, Yu et al 2018, whereas in apparently sporadic cases (Assie et al 2013, Emms et al 2016, Albiger et al 2017, Yu et al 2018) the frequency varies, depending on the characteristics of the studied cohort. Thus, the prevalence of ARMC5 mutations is about 40% (28-55%) in patients with overt CS, but much less, about 11%, in patients with subclinical CS (Table 1).…”
Section: Geneticsmentioning
confidence: 99%
“…This difference had an anatomical substratum, adrenals in patients carrying ARMC5 deleterious mutation were indeed larger and harbored a higher number of nodules , Albiger et al 2017). An ARMC5-damaging mutation or deletion was found to segregate in several families of PBMAH (Suzuki et al 2015, Bourdeau et al 2016. Interestingly, adrenal hyperplasia was associated with meningioma in one family carrying (p. A110fs*9) ARMC5 mutation (Elbelt et al 2015).…”
Section: Primary Bilateral Macronodular Adrenal Hyperplasia (Pbmah)mentioning
confidence: 98%
“…Paralelamente, analisamos a expressão gênica e proteica dos genes SLC2A1 e HK2, na tentativa de elucidar um possível mecanismo pelo qual ocorre o aumento da atividade metabólica, à semelhança do que ocorre nas neoplasias suprarrenais malignas (13) Ao longo dos anos, em busca de uma causa molecular da PMAH, foram identificadas mutações em pacientes diagnosticados com esta doença, como por exemplo mutações somáticas nos genes MC2R, GNAS, MEN1 (18), no entanto, sempre em casos isolados. Recentemente, estudos independentes demonstraram que mutações no gene armadillo repeat containing 5 (ARMC5) são uma causa frequente de PMAH, tanto na forma familial como na forma aparentemente esporádica da doença (8,(19)(20)(21)(22)(23)(24). Mais especificamente, mutações germinativas em heterozigose no ARMC5 foram identificadas em 38-55% dos pacientes com a doença em coortes diferentes (8,19).…”
Section: Manifestações Clínicasunclassified
“…De fato, se desconhece a real prevalência da forma familial da doença, uma vez que não é realizada uma avaliação sistemática dos parentes dos pacientes com PMAH. Até a presente data, foram descritas na literatura poucas famílias com a forma herdada da doença (8,19,21,(24)(25)(26).…”
Section: No Ambulatório De Suprarrenal Do Hospital Das Clínicas Da Faunclassified